2020
DOI: 10.1080/2331205x.2020.1716447
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation and bioassay-guided isolation of antihypertensive components of Senecio serratuloides

Abstract: Senecio serratuloides commonly referred to as "two day cure" is used in folk medicine for treating hypertension and wounds in South Africa. This study was aimed at isolating and testing the antihypertensive effects of bioactive compounds from S. serratuloides. Senecio serratuloides was serially extracted using solvents of increasing polarity. Phytochemical analysis, antioxidant capacity and antihypertensive properties of fractions were investigated. Bioactive compounds were isolated from ethyl acetate and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…Ethyl acetate is a secondary polar solvent and its extract has been reported to contain phytochemicals majorly alkaloids, saponins and some classes of phenols that play important roles as antibacterial agents and maybe the rationale behind the observed level of activity in TME fraction. This observation supports the findings of Tata et al 59, and Sakar et al 43 who reported similar observation in their respective studies. The variation in the zones of inhibition between the crude (Table 6), partitioned fraction (Table 8), and fractions obtained from the column (Table 10) may be due to a decrease in the concentration of the phytochemical constituents' present in these fractions as the purification processes progress.…”
Section: Resultssupporting
confidence: 92%
“…Ethyl acetate is a secondary polar solvent and its extract has been reported to contain phytochemicals majorly alkaloids, saponins and some classes of phenols that play important roles as antibacterial agents and maybe the rationale behind the observed level of activity in TME fraction. This observation supports the findings of Tata et al 59, and Sakar et al 43 who reported similar observation in their respective studies. The variation in the zones of inhibition between the crude (Table 6), partitioned fraction (Table 8), and fractions obtained from the column (Table 10) may be due to a decrease in the concentration of the phytochemical constituents' present in these fractions as the purification processes progress.…”
Section: Resultssupporting
confidence: 92%